KERAGAMAN GENETIK BURUNG MALEO (Macrocephalon maleo) BERDASARKAN POLIMORFISME PROTEIN DARAH - Hastarina, Rini (FAPETKAN UNTAD, 2016)
The objective of this research was to determine the genetic variation of the Maleo (Macrocephalon maleo) based on blood protein polymorphism. Material of the research was blood of Maleo coming from different original habitat, coastal and inland area. PAGE-TYLE (Polyacrilamide Gel Electrophoresis-Thin Layer Electrophoresis) was used in this research. Parameters observed were genotype at four locus Pre Albumin (PAlb), Albumin (Alb), Ceruloplasmin (Cp) and Transferrin (Tf). The obtained various data were used to analyze gene frequency, individual heterozygosity as well as average heterozygosity. The result showed that gene frequencies at allele A and B of four locus Maleo bothÂ in coastal and inland habitat were the same at PAlb locus and Tf locus, that was 0.5; Alb locus was 0.33 vs 0.67 and 0.67 vs 0.33, respectively; Cp locus was 0.5 vs 0.67 and 0.5 vs 0.33, respectively. Individual heterozygosity of four locus Maleo in coastal and inland habitat were the same at PAlb and TfÂ that was 0.5; Alb was 0.4555 respectively; Cp was 0.5 vs 0.4555 respectively. Average heterozygosity in coastal and inland Maleo were 0.3911 and 0.3822, respectively. In conclusion, Maleo in coastal and inland habitat showed the same value of diversity relativity due to uncontrolled assortative mating.Key words: Maleo (Macrocephalon maleo), genetic variation, polymorphism blood protein